1999
DOI: 10.1017/s0029665199001160
|View full text |Cite
|
Sign up to set email alerts
|

Introduction toin vivo31P magnetic resonance spectroscopy of (human) skeletal muscle

Abstract: fax +31 24 3540 866, email a.heerschap@rdiag.azn.nl 31 P magnetic resonance spectroscopy (MRS) offers a unique non-invasive window on energy metabolism in skeletal muscle, with possibilities for longitudinal studies and of obtaining important bioenergetic data continuously and with sufficient time resolution during muscle exercise. The present paper provides an introductory overview of the current status of in vivo 31 P MRS of skeletal muscle, focusing on human applications, but with some illustrative examples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 56 publications
(72 reference statements)
2
21
0
2
Order By: Relevance
“…1 H NMR of perchloric acid extracts shows that this is the case. Furthermore it had been shown that total creatine is proportional to creatine content in other circumstances [21,25]. Therefore, the conclusion drawn with 31 P NMR on muscle energetics (PCr, PCr:ATP ratio and PCr to γ-ATP flux) appears to be valid.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…1 H NMR of perchloric acid extracts shows that this is the case. Furthermore it had been shown that total creatine is proportional to creatine content in other circumstances [21,25]. Therefore, the conclusion drawn with 31 P NMR on muscle energetics (PCr, PCr:ATP ratio and PCr to γ-ATP flux) appears to be valid.…”
Section: Discussionmentioning
confidence: 93%
“…In our experiment, the rate constants k a and k b between PCr and γ-ATP and between β-ATP and β-ADP respectively were determined as: Ex vivo 1 H NMR spectroscopy Muscle energetics calculated from 31 P NMR spectroscopy parameters rely on hypotheses, one of which is that total creatine (PCr+creatine) content in muscle is strictly proportional to the NMR signal, regardless the circumstances. To make sure that total creatine content was constant in DEX-treated, PF and CON rats, we have measured this content in perchloric acid extracts with 1 H NMR spectroscopy, which is the reference technique [20,21].…”
Section: Animalsmentioning
confidence: 99%
“…In turn, macroscopic compartmentation is better described as partial volume effect and is a very common finding in MR spectroscopy and imaging. Different metabolite levels [55][56][57] and splitting of the resonance of inorganic phosphate 56,[58][59][60][61][62] may be the result of the inclusion of slow-and fast-twitch fibers in the sensitive volume of 31 P-MR spectra acquisition. An interpretation of this effect obviously can lead to physiological knowledge; however, since it does not contain specific information on cellular or subcellular order of tissue, it will not be discussed in detail here.…”
Section: Cellular and Subcellular Compart-mentation Transport Phenomenamentioning
confidence: 99%
“…La concentration d'ADP libre cytosolique ainsi que la production d'ATP par les voies oxydatives et non-oxydatives peuvent être déterminées. Conjuguée à la mise en oeuvre relativement simple d'antennes de surface posées directement en regard du segment d'intérêt, la spectroscopie du 31 P a contribué énormément à l'avancée des connaissances sur l'énergétique musculaire, sa régulation à l'exercice et les perturbations introduites par les pathologies (Chance et al 1986 ;Heerschap et al 1999 ;Argov et al 2000). À ce jour, la spectroscopie RMN n'a toutefois pas joué un role significatif comme outil d'évaluation des maladies neuromusculaires.…”
Section: Le Rôle De La Spectroscopie Rmn Du 31 P Comme Outil D'évaluaunclassified